Faculty Engagement in Using Teaching Learning Pedagogies of Digital Edge – Technology, Strategies & Challenges - Bansode, Rajesh; Modi, Niki; Das, Kriti; Lal, Sajjan Kumar (Journal of Engineering Education Transformations, 2025)
Since 2005, Our institute (TCET) has been dedicated to excellence in teaching learning practices, epitomized by its adoption of the ISO Quality Management System (QMS). This system is pivotal in ensuring exceptional products and services for its primary stakeholders, the students. By meticulously scrutinizing every aspect of its offerings, TCET guarantees consistent delivery of high quality. The integration of quality models into daily academic operations viz. 5W1H etc., in a structured through documented processes as a semester conduct, ensures rigorous adherence. Regular audits reinforce this commitment, while continuous monitoring and review drive ongoing improvement. Embracing Quality Assessment and Accreditation, TCET’s quality model is rooted in ISO standards, emphasizing customer satisfaction and a student-centric learning atmosphere in teaching learning practices. Structured around the PDCA cycle, the QMS provides a systematic approach [1] for process development and enhancement, guided by clear responsibilities and accountability. By integrating ISO standards and structured processes, TCET has cultivated a student centric learning environment that emphasizes innovation and interdisciplinary learning. Impact studies confirm tangible enhancements in education quality, reinforcing TCET’s reputation as a frontrunner in academic excellence. Looking ahead, TCET is committed to ongoing enhancement and surpassing standards in teaching and learning methodologies. The semester conduct ISO institutional process IP- 02 extends across all organizational functions, including interactions with regulatory bodies, students, and external providers. Quality Objectives include maintaining high-quality education, enhancing student satisfaction, and fostering innovation. Through innovative practices like Experiential Learning and Collaborative Learning, TCET enriches student abilities and promotes interdisciplinary learning. Impact studies demonstrate tangible improvements, including increased collaborations, publications, and technical skills. Embodying best practices, TCET places the student at the core of all activities, ensuring continuous performance improvement and consistently exceeding expectations through consistent delivery of various teaching learning pedagogies (TLP). The outcome result embodies the proof indicating the measurement through student satisfaction survey, continual practice of outcome based education, end semester result & PO attainment of the batch 2022-23 for effective faculty engagement in enriching TLP use of digital age.